Zigzag: Daniel Libeskind’s Jewish Museum in Berlin - Kamczycki, Artur (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
In The Meaning of Asymmetry in Jewish Art, Avigdor Poseq notes a historical tendency in Jewish art to depict Temple-related ritual objects asymmetrically, symbolizing their dislocation after the Temple’s destruction and the continued wait for the Messiah. Symmetry represents divine order and perfection, while asymmetry implies disruption and impermanence. This idea underpins Daniel Libeskind’s design of the Jewish Museum in Berlin (2000), with its fractured, zigzag structure evoking an incomplete process and broken continuity. The building becomes a metaphor for messianic hope, covenant renewal, and tikkun olam – the restoration of the world – interpreted through the lens of the Jewish Kabbalah.